Martes americana Pinel 1792 - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
9. American Marten Martes americana French: Martre d’Amérique / German: Fichtenmarder / Spanish: Marta norteamericana Taxonomy. Mustela americanus Turton, 1806, North America. The number of subspecies is debated and here we recognize eight. Subspecies and Distribution. M. a. americana Turton, 1806 — E Canada (Ontario & Quebec) anf NE USA. M. a. abietinoides Gray, 1865 — SW Canada (C British Columbia & SW Alberta) and NW USA (N Montana & Idaho). M. a. actuosa Osgood, 1900 — Alaska and NW Canada (N Alberta, N British Catan, Northwest Territories & Yukon). M. a. atrata Bangs, 1897 — NE Canada (Newfoundland and Labrador). M. a. caurina Merriam, 1890 — W Canada (W British Columbia) and USA (S Alaska & W Washington). M. a. humboldtensis Grinnell & Dixon, 1926 — SW USA (NW California). M. a. kenaiensis Elliot, 1903 — Alaska (Kenai Peninsula). M. a. nesophila Osgood, 1901 — SW Alaska and W Canada (islands off British Columbia, and perhaps along nearby mainland). Descriptive notes. Head-body 36-45 cm (males), 32-40 cm (females), tail 20-23 cm (males), 18-20 cm (females); weight 470-1250 g (males), 280-850 g (females), adult males are about 65% heavier than females. The American Marten has a long, slender body, with short limbs, bushy tail, and large rounded ears. The pelage ranges from light beige to dark brown, and often shows shades of orange. Many individuals have yellow to bright orange throat and upper chest patches. The head is pale gray and the legs and tail are almost black. The feet are fully furred, each digit has a strong claw. There are four pairs of mammae. The skull is long and narrow, with elongated auditory bullae. Dental formula: 13/3,C1/1,P4/4,M 1/2 = 38. Habitat. American Martens are found predominantly in mature conifer or coniferdominated mixed forests. Preferred habitats are mature old-growth spruce-fir communities, with greater than 30% canopy cover, a well-established understory of fallen logs and stumps, and lush shrub and forb vegetation. They avoid large open spaces such ...